STATIC CHARACTERISTICS ANALYSIS OF SPHERICAL HYBRID SLIDING BEARINGS BASED ON CFD - LIU ShiTan; SHEN JingFeng; WANG Jian (Jixie qiangdu)
Aiming at the lubrication characteristics of spherical hybrid sliding bearings（ SHSBs） for an ultra-high precision grinding machine,the Reynolds equations often adopt more assumptions,and the calculation accuracy cannot meet the design requirements of ultra-high precision bearings. The pressure and temperature field distribution characteristics of SHSBs was analyzed by CFD software based on N-S equations. And the variation law of structural parameters and working parameters on load capacity,flow and temperature rise,as well as the coupling effect between various parameters was explored. Based on this,the orthogonal experimental design method was used to obtain the optimal parameter combination of SHSBs under the premise of meeting the multi-objectives of high load and low temperature rise. The results show that these parameters significantly affect the bearing capacity and temperature rise of the bearing,and there are also cross-coupling effects. The analysis results are instructive for further research on the design of SHSBs.